2013
DOI: 10.1177/0021955x13504774
|View full text |Cite
|
Sign up to set email alerts
|

Lignin-based rigid polyurethane foams with improved biodegradation

Abstract: Rigid polyurethane (RPU) foams have been synthesized using lignin-based polyols obtained by oxypropylation of four distinct lignins (Alcell, Indulin AT, Curan 27-11P, and Sarkanda). Polyol formulations with two lignin/propylene oxide/catalyst content (L/PO/C) ratios were chosen (30/70/2 and 20/80/5). RPU foams have been prepared with a polyol component that incorporates the lignin-based one at contents ranging from 25 to 100%. A 100% commercial polyol-based (Lupranol® 3323) RPU foam was also prepared and used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 19 publications
0
43
0
1
Order By: Relevance
“…The apparent density for the foam with 10% lignin was the highest, increased by 14.2% relative to the control foam, while the foam with 15% lignin showed the lowest density of 0.047 g/cm −3 , which was 12.8% lower than the control foam. In general, for foams with similar cell wall thickness, density is known to decrease as cell size increases, which further influence mechanical properties [32]. Therefore, the low density for the 15% lignin foam is due to its large cell size as evidenced by the SEM image (Figure 1(d)).…”
Section: Apparent Density and Mechanical Propertiesmentioning
confidence: 98%
“…The apparent density for the foam with 10% lignin was the highest, increased by 14.2% relative to the control foam, while the foam with 15% lignin showed the lowest density of 0.047 g/cm −3 , which was 12.8% lower than the control foam. In general, for foams with similar cell wall thickness, density is known to decrease as cell size increases, which further influence mechanical properties [32]. Therefore, the low density for the 15% lignin foam is due to its large cell size as evidenced by the SEM image (Figure 1(d)).…”
Section: Apparent Density and Mechanical Propertiesmentioning
confidence: 98%
“…3,6,7 On the other hand, the macromolecular structure of lignin can be used for the preparation of polymeric materials. Herein, many possible applications are proposed in the literature; for instance, the use of lignin as polyol for polyurethanes 8,9,10 or as phenol substitute in phenolic resins. 11,12 Furthermore, lignin can be used in blends to increase mechanical stability or biodegradability.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of a higher molecular weight, less degradation, and a higher bark fraction due to a higher biomass conversion yield, have all led to a polyurethane network that was superior to that made from a liquefied bark-based polyol. Furthermore, the oxypropylated bark showed improved mechanical properties over oxypropylated lignin PUFs with the highest reported elastic modulus of 3.41 MPa (Cateto et al, 2014); oxypropylated kraft lignin PUFs with a highest reported strength value of 140 kPa and modulus of 3.41 MPa (Li and Ragauskas, 2012); and a lower modulus, but comparable strength to PUFs made from oxypropylated organo-solv lignin (Arshanitsa et al, 2013). The oxypropylated bark PUF however had a lower elastic modulus and strength than foams made from liquefied starch that was then oxypropylated (Yoshioka et al, 2013).…”
Section: Foaming and Compression Testingmentioning
confidence: 98%